The Effect of Gut Microbiome Composition on Human Immune Responses: An Exploration of Interference by Helminth Infections - Martin, Ivonne; Kaisar, Maria M. M.; Wiria, Aprilianto E.; Hamid, Firdaus; Djuardi, Yenny; Sartono, Erliyani; Rosa, Bruce A.; Mitreva, Makedonka; Supali, Taniawati; Houwing-Duistermaat, Jeanine J.; Yazdanbakhsh, Maria; Wammes, Linda J. (Frontiers in Genetics, 2019)
Background Soil-transmitted helminths have been shown to have the immune regulatory capacity, which they use to enhance their long term survival within their host. As these parasites reside in the gastrointestinal tract, they might modulate the immune system through altering the gut bacterial composition. Although the relationships between helminth infections or the microbiome with the immune system have been studied separately, their combined interactions are largely unknown. In this study, we aim to analyze the relationship between bacterial communities with cytokine response in the presence or absence of helminth infections. Results For 66 subjects from a randomized placebo-controlled trial, stool and blood samples were available at both baseline and 21 months after starting three-monthly albendazole treatment. The stool samples were used to identify the helminth infection status and fecal microbiota composition, while whole blood samples were cultured to obtain cytokine responses to innate and adaptive stimuli. When subjects were free of helminth infection (helminth-negative), increasing proportions of Bacteroidetes was associated with lower levels of IL-10 response to LPS (estimate (95% confidence interval (CI)) -1.96 (-3.05, -0.87) ). This association was significantly diminished when subjects were helminth-infected (helminth positive) (p-value for the difference between helminth-negative versus helminth-positive was 0.002). Higher diversity was associated with greater IFN-γ responses to PHA in helminth-negative (0.95 (0.15, 1.75); versus helminth-positive -0.07 (-0.88, 0.73), p-value = 0.056) subjects. Albendazole treatment showed no direct effect in the association between bacterial proportion and cytokine responses, although the Bacteroidetes’ effect on IL-10 responses to LPS was lower in the albendazole-treated group (-1.74 (-4.08, 0.59) versus placebo (-0.11 (-0.84, 0.62); p-value = 0.193). Conclusion We observed differences in the relationship between gut microbiome composition and immune responses when comparing individuals infected or uninfected with geohelminths. Although these findings are part of a preliminary exploration, the data support the hypothesis that intestinal helminths may modulate immune responses, in unison with the gut microbiota. Trial registration: ISRCTN, ISRCTN83830814. Registered 27 February 2008 - Retrospectively registered, http://www.isrctn.com/ISRCTN83830814